Scars of the Past – Stories: Creating A Short Story Collection Highlighting Childhood Emotional Neglect and Its Impacts in Adulthood - Winona Nathania Rahardjo; Stefanny Irawan (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
Childhood Emotional Neglect (CEN) is described as a parent’s failure to respond enough to their child’s emotional needs. Although the effects can be severe, it is rarely studied compared to other kinds of childhood abuse and maltreatment. The writers hope to raise awareness about the topic through a short story collection which consists of four stories. Each story shows different types of emotionally neglectful parents, its impacts on the victims as adults, and how they overcome their situation using Dr. Jonice Webb’s empirical insights on CEN as a theoretical framework. The protagonists: Amanda, Brian, Christine, and Daniel, are people in their early twenties who go through their lives trying to deal with the impact of childhood emotional neglect that their parents gave them. The stories show a few types of emotionally neglectful parents: the combination of the narcissistic parent and the achievement/perfection focused parent, the permissive parent, the workaholic parent, and child as parent. The impacts in adulthood materialize in these stories include hiding emotions and lack of self-love, lack of self-discipline, lack of self-esteem, and being overly responsible. The solutions pursued by the main characters are learning to say no, improving their sense of self-discipline, self-soothing, and trying to put themselves first.